Spatial Lipidomics of Lesioned Mouse Striatum: Modelling Neuroinflammatory Mechanisms in MS - Jansma, Silke (My University, 2025)
This thesis investigates changes in lipid composition in the mouse striatum following the induction of multiple sclerosis-like neuroinflammatory lesions. Using Mass Spectrometry Imaging (MSI) supported by hypothesis testing and Principal Component Analysis (PCA), spatial lipid alterations were assessed within and across hemispheres in lesion and sham-control animals. Lesion-associated lipid signatures included increases of ceramides, phosphatidylcholines (PCs), and phosphatidylethanolamines (PEs), consistent with inflammatory activation, membrane remodelling, and neurodegeneration. These changes were most apparent when comparing the lesioned striata to the sham control striata with hypothesis testing. PCA further identified lipid species that, while not always statistically significant in isolation, contributed strongly to overall variance, suggesting coordinated biochemical responses to injury. The inclusion of broad anatomical regions may have introduced noise and obscured some of the lesion-specific lipid changes. Despite these limitations, the study demonstrates the utility of spatial lipidomics for detecting subtle, region-specific metabolic disruptions in models of neuroinflammation. These results suggest that MSI-based lipid profiling holds promise for identifying biomarkers and provides mechanistic insights into neuroinflammation and multiple sclerosis.
Keywords: Neuroinflammation, Multiple Sclerosis, Lipidomics, Mass-Spectrometry Imaging, MS-lesion Study, Neurodegenerative Disorder